2014
DOI: 10.2174/157339710904140417125803
|View full text |Cite
|
Sign up to set email alerts
|

Digital Ulcers in Systemic Sclerosis – How to Manage in 2013?

Abstract: Digital ulcers (DUs) are among the most frequent and disabling vascular complications in patients with systemic sclerosis (SSc). The etiology and pathogenesis of DUs differs depending on the lesion localization. For this reason the underlying etiologic and pathogenetic factors will guide the therapeutic decision. The main pathogenic mechanism that contributes to the development of fingertip DUs is ischemia owing to SSc-related vasculopathy. DUs over bony prominences are mainly a result of skin fibrosis, epider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…La Montagna et al (2002) have observed digital ulcers of the hands in 43% of cases vs 8% prevalence of the feet (p < 0.001) [11]. Similar are the results from an own study (Lambova et al, 2013), in which the prevalence of digital ulcers of the hands was 35% (21/60) vs 10% (6/60) -prevalence of the toes (p < 0.05) [10].…”
Section: Introductionsupporting
confidence: 75%
See 2 more Smart Citations
“…La Montagna et al (2002) have observed digital ulcers of the hands in 43% of cases vs 8% prevalence of the feet (p < 0.001) [11]. Similar are the results from an own study (Lambova et al, 2013), in which the prevalence of digital ulcers of the hands was 35% (21/60) vs 10% (6/60) -prevalence of the toes (p < 0.05) [10].…”
Section: Introductionsupporting
confidence: 75%
“…We have previously reported personal experience with administration of subcutaneous low-molecular heparin for one month with switching on low-dose aspirin after documented improvement in SSc patients with digital gangrene [10]. Official recommendations about the administration of antiplatelet drugs (e. g., low-dose aspirin, clopidogrel) and anticoagulants (heparin) in the therapeutic protocol of digital ulcers in SSc are absent and their use is based on experts' opinion [25,26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Systemic sclerosis (SSc) is a prototypic fibrotic disease that causes tissue and vascular fibrosis in the skin and internal organs including heart, lungs, kidneys and gastrointestinal tract 1 2. Tissue fibrosis typically starts in the skin at the level of hands and feet3 and progresses through the arms and thighs to eventually involve the chest and abdomen in the most severe cases (diffuse cutaneous SSc) 1…”
Section: Introductionmentioning
confidence: 99%